Therapeutic Drug Monitoring and Pharmacogenetic Testing in Northern China - Zhang, Chunyan; Lei, Jing; Liu, Yi; Wang, Yu; Huang, Lin; Feng, Yufei (Frontiers in Pharmacology, 2021)
Background: Therapeutic drug monitoring (TDM) and Pharmacogenetic (PGx) testing are widely applied as approaches to enhance individualized (personalized) pharmacotherapy. Little is known about TDM and PGx testing services in China. This study is aimed to describe the TDM and PGx testing services in northern China, and to lay the foundation for improvement of these services. Methods: We developed an electronic survey using online software and disseminated it to 32 public hospitals in northern China from May to July 2019. The data were analyzed using the Statistical Package for Social Sciences (SPSS) program (Ver.27.0). Results: We collected 29 of the 32 questionnaires (90.6% response rate) from the public hospitals in 7 provinces of northern China. Twenty-two public hospitals (76%) utilized TDM; immune suppressants, antiepileptic drugs and anti-infective drugs were the main drugs monitored. The hospitals not providing TDM service were traditional Chinese medicine hospitals and hospitals with a smaller number of hospital beds. Seventeen public hospitals (58.6%) had PGx testing programs. The hospitals that did not provide PGx testing service had a smaller number of hospital beds and fewer daily outpatients. Conclusions: TDM is available in the vast majority of public hospitals in northern China but mainly in tertiary hospitals. PGx testing, a more recent approach, is less widely available. We recommend that more hospitals be encouraged to provide TDM and PGx testing services and more efforts be directed at quality control, delivery of results and counseling of patients based on those results.